Prevention of Mist Formation in Amine Based Carbon Capture: Field Testing Using a Wet ElectroStatic Precipitator (WESP) and a Gas-Gas Heater (GGH). (July 2017) - Mertens, Jan; Khakharia, P.; Rogiers, Pieter; Blondeau, J.; Lepaumier, H.; Goetheer, E.; Schallert, B.; Schaber, K.; Moretti, I.
Abstract: This study presents the results of two field tests that aimed at evaluating two countermeasures (WESP and GGH) to avoid acid mist formation. A WESP is shown to be very efficient for the removal of nuclei from the flue gas (100% efficient) and thus can prevent aerosol formation inside an amine based absorber. This is however only valid in the absence of SO2 in the flue gas entering the WESP. A decreasing WESP efficiency is noted in the presence of SO2 with increasing voltages as a result of newly formed aerosols inside the WESP. This implies that no or very low levels of SO2 should be present in the flue gas entering the WESP. Since most of the amine carbon capture installations have a pre-scrubber (usually using NaOH to remove residual SO2 in the flue gas leaving the power plant's Flue Gas Desulphurisation) in front of their amine absorber, the WESP must be installed behind this pre-scrubber and not in front of it. Having a Gas-Gas Heater (or any type of flue gas cooling such as a Low Temperature Heat Exchanger) installed upstream of the wet scrubbing may prevent homogenous nucleation and thus prevent the conversion of H2 SO4 into sulfuric acid aerosols and consequently mist formation issues in the amine based carbon capture installation. Which option to choose amongst the two countermeasures presented in this study will depend on whether a new built installation is being considered or whether a carbon capture is planned as a retrofit into an existing installation.